Ta’ṡīru Ta‘allumi al-Lugah al-‘Arabiyyah ‘alā Mustawā Ma‘rifati al-Qirā’ah wa al-Kitābah Ladā Ṭullābi al-Madāris al-Ṡānawiyyah ad-Dīniyyah fī Madīnah Sīrībūn: The Effect of Arabic Language Learning on the Literacy Level of Madrasah Aliyah Students in Cirebon City - Lia Maulida Afifah; Wahyudin; Yanti Kusnawati (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2025)
This study analyses the effect of Arabic language learning on the literacy levels of high school students in Cirebon using a quantitative approach and simple linear regression. The population of this study consisted of students from seven Madrasah Aliyah in Cirebon, with a sample of 69 students. Data were collected through questionnaires on the quality of Arabic language learning and students' literacy tests, which were tested for validity and reliability. The regression analysis results showed a regression coefficient of 0.86, indicating that a 1-unit increase in Arabic language learning is associated with an 86% increase in literacy. The Pearson correlation test showed a powerful relationship with a value of 0.899. The coefficient of determination test (R² = 0.808) indicated that 80.8% of the variation in reading and writing literacy could be explained by Arabic language learning. The results of this study show that quality Arabic language learning can improve students' reading and writing literacy. Keywords: Arabic, Arabic learning, Literacy